Synthesis, crystal structure, DFT and Hirshfeld surface analysis of 4-fluoro-N-(1,3-dioxoisoindolin-2-yl)benzamide - Elancheran, Ramakrishnan; Karthikeyan, Balakrishnan; Srinivasan, Subramanian; Krishnasamy, Kuppusamy; Kabilan, Senthamaraikannan (European Journal of Chemistry, 2023)
The 4-fluoro-N-(1,3-dioxoisoindolin-2-yl)benzamide was synthesized by the reaction of 4-fluorobenzohydrazide with phthalic anhydride in acetic acid. The compound was characterized by analytical instruments like FT-IR and NMR. The three-dimensional structure of the title compound was further confirmed by single-crystal X-ray diffraction study. In addition to the experimental study, theoretical calculations were performed to explore the molecular structure in order to analyze experimental and theoretical findings. The title compound crystallizes in the monoclinic space group P21/n as determined by the X-ray diffraction investigation, crystal data for C15H9FN2O3·H2O: a = 14.094(6) Å, b = 7.248(3) Å, c = 14.517(6) Å, β = 105.116(14)°, V = 1431.6(10) Å3, Z = 4, T = 298(2) K, μ(MoKα) = 0.112 mm-1, Dcalc = 1.402 g/cm3, 37521 reflections measured (4.684° ≤ 2Θ ≤ 60.6°), 4225 unique (Rint = 0.0517, Rsigma = 0.0311) that were used in all calculations. The final R1 was 0.0537 (I > 2σ(I)) and wR2 was 0.1501 (all data). The N-H···O and O-H···O hydrogen bonds linking molecules in the crystal form a three-dimensional framework structure. The electronic states and molecular properties of the title compound were determined using computational studies, like density functional theory and Hirshfeld surface analysis.